Factors Associated with Successful Treatment Outcomes among Drug Addicts in the Drug Rehabilitation Clinic of Ban Miang Sub-district Health Promoting Hospital - Sarasaen, Namkang (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2026)
This cross-sectional survey research aimed to investigate factors associated with successful drug addiction treatment outcomes at the Drug Treatment Clinic, Ban Miang Sub-district Health Promoting Hospital, Tha Li District, Loei Province. The study population consisted of 53 drug patients who received treatment during fiscal years 2021–2023. Research instruments included a personal information questionnaire, Social Support Questionnaire (SSQ-12), Family Assessment Device (FAD), Social Stigma Scale (SSDS), Helping Alliance Questionnaire (HAQ-II), and WHOQOL-BREF. Data were analyzed using descriptive statistics, Chi-square test, Pearson’s correlation coefficient, and Stepwise Multiple Regression Analysis. The majority of participants were male (77.36%), with a mean age of 39.70 years (S.D. = 9.47), primary education level (54.72%), temporary employment (58.49%), methamphetamine as the primary substance (98.11%), and 4–6 years of drug use duration (54.70%). Treatment completion rate was 88.70%, while the one-year relapse rate was 79.20%. Factors significantly associated with treatment completion (p<0.05) included employment status, duration of drug use, and treatment attendance consistency. Factors significantly associated with non-relapse within one year (p<0.05) were social support and family relationships. Multiple regression analysis revealed that employment status and family relationships predicted treatment completion, while social quality of life and family participation predicted one-year abstinence. This study identified key factors associated with drug addiction treatment success in a primary care context, providing an evidence base for developing community-appropriate treatment models. Strengthening employment support, family involvement, and social networks are critical strategies for improving treatment outcomes and reducing relapse rates in sub-district health promoting hospitals.